Towards Urban Mobility Designs: En Route in the Functional City - Lanng, Ditte Bendix; Harder, Henrik; Jensen, Ole B. (Proceedings from the Annual Transport Conference at Aalborg University, 2012)
Functionalist traffic design aims at a rational organisation of movement from A to B in a segregated and uniform physical environment. Such urban areas have been criticized for being exclusively functional and lacking sensuous and social qualities. Recent research on mobilities challenges the more instrumental understanding of movement that underlies such traffic design. This research indicates that instrumental movement is only one aspect of ordinary journeys laden with meaning and experience to the wayfarers. In the paper we explore how we could think of the design of transit sites, if we operate insights on functional urban planning, on embodied practices and experiences of wayfaring, and on concrete small scale design concerns. We emphasise an integrated design agenda for those ordinary transit sites which is concerned with functional issues as well as the quality of life on the ground for the wayfarers who use the site. The data for our work concerns a transit site in the 1970s urban district of Aalborg Øst, Denmark. We set out by introducing our approach to the site. Second, we examine the functional layout of the transit site in Aalborg Øst and outline the design challenge which we are concerned with. Third, we introduce an embodied mobile perspective through insights from the mobilities turn. Fourth, through our own journey experience en route we present a mapping of the transit site. We conclude by outlining a few propositions on the design challenge and design potentials, in relation to re-conceptualisation of the transit site, to mapping, and to design intervention. These propositions form part of our on-going work with urban mobility designs.